THE MODEL OF SOCIAL SUPPORT OF PEOPLE IN THE EMPOWERMENT OF YOUTH AS AN EFFORT TO INCREASE SOCIAL FUNCTION - Astutik, Juli; Sugiharto, Aan; Abidin, Zaenal (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2022)
Abstract. This research was conducted to produce findings of peer social support models in adolescent empowerment to improve the social functioning of adolescent victims of drug abuse in Jabung District, Malang Regency. This research was conducted with a qualitative approach, descriptive type. The research subjects were determined purposively. Primary data is obtained through interviews, while secondary data is obtained from journals, print media, documents, articles, and literature. Data analysis is done by text analysis, analyzing what is implied in the data from both primary and secondary data collection results. Peer social support in empowering adolescents as an effort to improve the social functioning of adolescent victims of narcotics abuse in Jabung District, Malang Regency, includes (1) Emotional Support through activities of giving attention, caring, support, and empathy, (2) Award Support: giving appreciation in the form praise, giving rewards, (3) Instrumental Support: providing direct facilities and performance needs, (4) Information Support: Providing knowledge about the health and dangers of narcotics abuse, religious spirituality, (5) Social Network Support: building togetherness, cohesiveness, and mutual sharing. Peer social Support results in social functioning for adolescent victims of narcotics abuse so that: they 1) can fulfill their own daily needs, 2) can overcome their problems, 3) can carry out social roles both in the family and in the surrounding community, and 4) can develop self.Keywords: social Support, Narcotics Abuse, Social functioning Abstrak. Penelitian ini dilakukan dengan tujuan untuk menghasilkan temuan model dukungan sosial teman sebaya dalam pemberdayaan remaja sebagai upaya meningkatkan keberfungsian sosial remaja korban penyalahgunaan narkotika di Kecamatan Jabung, Kabupaten Malang. Penelitian ini dilakukan dengan pendekatan kualitatif, jenis deskriptif. Subyek penelitian ditentukan secara purporsive. Data primer diperoleh melalui wawancara, sedangkan data sekunder diperoleh dari jurnal, media cetak, dokumen, artikel, maupun literatur. Sedangkan analisis data dilakukan dengan analisis teks, dengan cara menganalisis hal yang tersirat dan tersurat dalam data hasil pengumpulan data baik secara primer maupun sekunder. Dukungan sosial teman sebaya dalam pemberdayaan remaja sebagai upaya meningkatkan keberfungsian sosial remaja korban penyalahgunaan narkotika di Kecamatan Jabung, Kabupaten Malang, meliputi: (1) Dukungan Emosional, melalui aktivitas pemberian perhatian, kepedulian, dukungan, empati (2) Dukungan Penghargaan: memberi apresiasi berupa pujian, pemberian reward, (3) Dukungan Instrumental: penyediaan kebutuhan fasilitas dan kinerja langsung, (4) Dukungan Informasi: Memberi pengetahuan tentang kesehatan dan bahaya penyalahgunaan narkotika, spiritual keagamaan, (5) Dukungan Jaringan Sosial: membangun kebersamaan, kekompakan dan saling sharing. Dari dukungan sosial teman sebaya ini menghasilkan keberfungsian sosial bagi remaja korban penyalahgunaan narkotika sehingga: 1) mampu memenuhi sendiri kebutuhannya sehari-hari, 2) mampu mengatasi masalahnya, 3) mampu melaksanakan peran sosial baik dalam keluarga maupun masyarakat sekitarnya dan 4) memiliki kemampuan mengembangkan diri sendiri.Kata kunci: Dukungan sosial, korban penyalahgunaan Narkotika, Keberfungsian sosial.